ANALYSIS SYSTEM AND EVALUATION OF KRI ELEMENT REDUCTION OF TASKS AS A MEANS OF NATIONAL DEFENSE - Didit Herdiawan; Joni Widjayanto; Benny Sukandari; Okol Sri Suharyo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
KRI is one of the main components possessed by the Indonesian Navy which has the main task of security and national defense at sea. The Termination of Operation KRI over the age of 40 results in a lack of existing KRI, so there is a need for research that represents an evaluation and analysis of the work system so that the main tasks can still be carried out. The SWOT and CIPP analysis in this study aims to identify several factors that influence the achievement of the main tasks. The results obtained are in Quadrant I (+; +) which states the status